2017
DOI: 10.1515/bjdm-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology, diagnosis and treatment of Ankyloglossia

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These issues encompassed articulation disorders and difficulties in the range of articulation that adversely affected speech intelligibility, although the specific sounds involved were not detailed [33]. Greek authors also noted in their review paper that individuals diagnosed with ankyloglossia encountered challenges with the articulation of sounds like "t, d, th, l, s" [42]. Some authors, such as Wang et al [43], in a review article based on the analysis of 16 studies on the impact of ankyloglossia on articulation problems, concluded that there is no definitive correlation between tongue frenulum shortening and speech disorders.…”
Section: Effect Of Ankyloglossia On Speech Abnormalities and Dysgloss...mentioning
confidence: 99%
“…These issues encompassed articulation disorders and difficulties in the range of articulation that adversely affected speech intelligibility, although the specific sounds involved were not detailed [33]. Greek authors also noted in their review paper that individuals diagnosed with ankyloglossia encountered challenges with the articulation of sounds like "t, d, th, l, s" [42]. Some authors, such as Wang et al [43], in a review article based on the analysis of 16 studies on the impact of ankyloglossia on articulation problems, concluded that there is no definitive correlation between tongue frenulum shortening and speech disorders.…”
Section: Effect Of Ankyloglossia On Speech Abnormalities and Dysgloss...mentioning
confidence: 99%
“…There are reports of lingual frenum which does not recede as the growth advances and leads to tongue immobility. [ 2 3 ] This causes ankyloglossia (AG) or tongue-tie. AG can be an isolated finding in routine clinical examinations in children.…”
Section: Introductionmentioning
confidence: 99%